Seasonal variations in swimming force and training adaptation - Havriluk, R. (Journal of Swimming Research, 2013)
Gauging the optimal workload is a challenge for swim coaches. This study was designed to address whether seasonal handforce variations provide information for adjusting the workload to maximizethe training effect. Nine national caliber swimmers from a team known for training with a substantial workload participatedin the study. The swimmers were tested seven times over an eight month season. The average hand force over a 10 m swim at maximum swimming velocity was calculated for each trial. Each swimmer had a depressed hand force value in the middle of the season ascompared to the baseline at the beginning of the season. Each swimmer's force value was elevated at the end of the season as compared to the middle of the season. However, only five of the nine swimmers (55%) had a higher force value at the end of the season as compared to the baseline.The results suggest that a workload that is too severe (because of training distance and/or intensity) may not allow swimmers to recover enough to improve performance. Periodic hand force testing can provide feedback about training adaptation, both to optimize performance and minimize the risk of illness and injury.